Culture & imperialism - Said, Edward W. (London Vintage, 1994)
A landmark work from the intellectually auspicious author of Orientalism that explores the long-overlooked connections between the Western imperial endeavor and the culture that both reflected and reinforced it.
Overlapping territories, intertwined histories -- Consolidated vision -- Resistance and opposition -- Freedom from domination in the future.
Originally published: London : Chatto & Windus Ltd, 1993.
Includes bibliographical references (pages 409-432) and index.
Keywords: European literature -- History and criticism -- Theory, etc; Literature -- History and criticism -- Theory, etc; Imperialism in literature; Colonies in literature; Politics and culture